2017
DOI: 10.1007/978-981-10-4086-3_145
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Diabetic Patients with a Remote Patient Monitoring Systems

Abstract: Abstract-In order to achieve better self-control of their diabetes and to decrease long-term risks of complications, diabetic patients monitor several different parameters on a day-to-day basis. These parameters, such as blood glucose level, insulin intake, weight, diet, exercise and physical activity, blood pressure, can be easily acquired using IT technologies without oppressing the patient with handwritten diaries. At the same time, healthcare professionals are provided with the data on time and can interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The symbol () indicates that the research paper uses the checked technology and the opposite is indicated by the symbol (). [15] Chronic diseases [2] Cardiovascular [26] Heart diseases [152] Ubiquitous monitoring system [28] Pain assessment [29] Heart diseases [40] Knees rehabilitation [153] Vital signs gathering and processing [46] Chronic diseases [47] Hypertension [57] Tracking daily activities [61] EXP carried on healthy volunteers [92] Context aware monitoring [77] Diabetes and Diet monitoring [96] Heart diseases [97] Diabetes [90] Diabetes [93] Mental disorder [154] Chronic diseases [155] Monitor patients with depression [131] Cardiovascular diseases [156] Hypertension, hypotension [157] Diabetes [158] Heart diseases [159] Knee arthroplasty [160] Elderly [161] Diabetes [162] Parkinson's disease [106] Fall detection [117] Diabetes [116] Alzheimer's Currently, many health monitoring projects and applications have been initiated that use different architectures. Health monitoring systems are heterogeneous and have been developed for various diseases and disabilities.…”
Section: Study Resultsmentioning
confidence: 99%
“…The symbol () indicates that the research paper uses the checked technology and the opposite is indicated by the symbol (). [15] Chronic diseases [2] Cardiovascular [26] Heart diseases [152] Ubiquitous monitoring system [28] Pain assessment [29] Heart diseases [40] Knees rehabilitation [153] Vital signs gathering and processing [46] Chronic diseases [47] Hypertension [57] Tracking daily activities [61] EXP carried on healthy volunteers [92] Context aware monitoring [77] Diabetes and Diet monitoring [96] Heart diseases [97] Diabetes [90] Diabetes [93] Mental disorder [154] Chronic diseases [155] Monitor patients with depression [131] Cardiovascular diseases [156] Hypertension, hypotension [157] Diabetes [158] Heart diseases [159] Knee arthroplasty [160] Elderly [161] Diabetes [162] Parkinson's disease [106] Fall detection [117] Diabetes [116] Alzheimer's Currently, many health monitoring projects and applications have been initiated that use different architectures. Health monitoring systems are heterogeneous and have been developed for various diseases and disabilities.…”
Section: Study Resultsmentioning
confidence: 99%
“…We proposed a deep learning model based on X-rays of the chest and transfer learning, to classify the patient as either infected or normal, and we achieved promising results. Monitor patients with depression [36] Cardiovascular diseases × [108] Heart failure × [109] Parkinson × × [110] Congestive heart failure × [111] Hypertension, hypotension × [112] Diabetes × × × [113] Heart diseases × × × [114] Heart diseases × × [115] Elderly × [116] Diabetes × × × [117] Parkinson's disease × × [118] Chronic diseases × × [58] Diabetes × × ×…”
Section: Discussionmentioning
confidence: 99%
“…In a context of diabetic patients monitoring [27], setting up tools for accident detection is not possible without considering the necessary role that the physician must have. The aim is to design a system for assisted monitoring and diagnosis that will provide specialists with the necessary information for identifying the diabetes type of patients.…”
Section: Classification By Inductive Learningmentioning
confidence: 99%